HUBUNGAN KESULITAN BELAJAR MATEMATIKA TERHADAP KEMAMPUAN KONEKSI MATEMATIKA PADA SISWA SMK KARTIKA 1 SURABAYA - Elok Hidhayati Hartanti (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2016)
This research is motivated by the low ability students' mathematical connections. Mathematical reasoning and connections are two basic mathematical ability that must be mastered middle school students. However, many students have problems and learning difficulties in solving mathematical problems. Through the process of mathematical connections, conceptual thinking and students' horizons will be broader, the students will have the skills to solve problems and make decisions. The problem of this research is " Is there any connection to the students' mathematics learning difficulties mathematical connection capability? ". Subjects in these criteria is a class XI student of SMK Kartika Accounting 1 Surabaya. Data obtained by questionnaire to measure students' learning difficulties and then given treatment for the provision of learning achievement test items to get valid data. Based on the analysis of data by using the formula Pearson product moment is known H_0 is no relationship difficulty learning mathematics against the ability to connect mathematics to the students of class XI AK-1 SMK Kartika 1 Surabaya while the H1 is no relationship difficulty learning mathematics against the ability to connect mathematics to the students of class XI AK-1 SMK Kartika 1 Surabaya. Of the formula product moment correlation can be obtained rhitung with significance level of 5% showed greater than the value rtabel = 0.344 and rhitung = 0.45; where r_hitung> r_tabel or 0.45> 0.344, it can be concluded that learning difficulties affect the ability of students' mathematical connections. Keywords: Learning Difficulties, Mathematics Connection Capability